KERONCONGKU, NGRONCONGI - Bayu Raditya Prabowo (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
ABSTRACT Keroncong music has a basic concept of musical achievement that is often expressed by keroncong artists with the word "ngroncongi". Ngroncongi is a term that refers to the Java language. Keroncong becomes the basic word, which at the beginning of the word is affixed "Ng- "  and at the end the word gets "-i", so initially keroncong is a noun, turning into an adjective after it turns into "ngroncongi". Ngroncongi is a musical aspect that becomes an indication of keroncong music characteristic. Ngroncongi will be achieved when it reaches the aesthetic and keroncong culture. Musicality which is "ngroncongi" is constructed by several musical elements such as, samen spelen; ngglali; nyendaren; mbesut; luk; gojek; isen-isen; mbanyumili; and sintiran. Those elements are synergized to accommodate the concept of "ngroncongi". The elements of rhythmic pattern are sintiran, mbanyumili, and gojek. The elements for ornamentation are ngglali; mbesut; luk; nyendaren; and isen-isen. While the element of "samen spelen" is for a musical interaction between players by giving each other musical communication. These elements found from the emissive knowledge of keroncong players who are represented in musical way to build musicality which is called "ngroncongi". Kata kunci : Keroncong, Ngroncongi, Musikalitas